2002
DOI: 10.1007/bf03178371
|View full text |Cite
|
Sign up to set email alerts
|

Compliance testing of medical diagnostic x-ray equipment: three years’ experience at a major teaching hospital in Western Australia

Abstract: The impact of a formal compliance testing program has been evaluated three years post-implementation on a major teaching hospital (Sir Charles Gairdner Hospital) with 46 x-ray tubes located throughout 37 rooms. The mandatory program, implemented by the statutory authority in January 1997, called for all medical (including chiropractic and dental) equipment used in human diagnosis to be tested at prescribed frequencies using established protocols. The application of the required test methods demonstrated variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…These parameters are reflected in the reports, which show that only 77.27% of installations inspected in the last year of the study complied with these official recommendations, although this is a 15.6% improvement over the initial situation. A study carried out by ZHANG and co-workers (23), showed that the use of a rectangular collimator, together with a cone distance of 20 cm and 2 mm Al filter is sufficient to reduce the dose absorbed by the patient by 90%. Our finding show that the mean radiation dose for an upper molar in Spain was 3.84 for 1996-97, a value which had fallen to 3,28 mGy six years later.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters are reflected in the reports, which show that only 77.27% of installations inspected in the last year of the study complied with these official recommendations, although this is a 15.6% improvement over the initial situation. A study carried out by ZHANG and co-workers (23), showed that the use of a rectangular collimator, together with a cone distance of 20 cm and 2 mm Al filter is sufficient to reduce the dose absorbed by the patient by 90%. Our finding show that the mean radiation dose for an upper molar in Spain was 3.84 for 1996-97, a value which had fallen to 3,28 mGy six years later.…”
Section: Discussionmentioning
confidence: 99%
“…79 The mandatory program called for all medical (including chiropractic and dental) equipment used in human diagnosis to be tested at prescribed frequencies using established protocols. The application of the required test methods demonstrated various noncompliance issues.…”
Section: General Health Settingsmentioning
confidence: 99%